Changes in pupillary light reflex following competitive rugby union - Barnes, A.; Kirk, C.; Hill, R.; Bowden, B.; Mercer, J. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Automated pupil light reflex (PLR) is a valid indicator of dysfunctional autonomic brainfunction following traumatic brain injury and may be a useful tool to triage patients [1]. Rugby union is characterised by repeated head accelerations, with high head acceleration events occurring more frequently in elite men`s forwards than backs [2]. PLR may offer a more sensitive and objective means of detecting signs of brain dysfunction resulting from head accelerations without diagnosed concussion and may reduce the need for clinical judgments to inform player management. This study aimed to examine the impact of a competitive match on PLR variables. METHODS: Twenty-nine adult male rugby players (16 Forwards, 13 Backs) playing level 4 rugby in the English league structure took part in the study. PLR of both eyes were measured pre and post a competitive match using a Neuroptic NPi-200. Pupillometry values including the Neurological Pupil Index (NPi), mean constriction velocity (CV), max constriction velocity (MCV), and dilation velocity (DV) were obtained. Differences between left and right eye were analysed pre- and post-match using a paired t-test. The averages of both eyes together were compared pre- and post-match, and between forwards and backs using a two-way mixed ANOVA. RESULTS: The difference in DV between the left and right eye increased post-match (0.3± 0.1824 mm· s-1)compared to pre-match ( 0.14± 0.1324 mm·s-1, p=0.05). There was a significant main effect of match on both NPi (pre= 3.8 ±0.4 AU vs post=3.5 ±0.4 AU, p=0.005) and DV (pre=1.25 ±0.24 mm·s-1 vs post=1.12± 0.18 mm·s-1, p=0.02). No main effect of position was seen for any variables, nor were there any observed interaction effects. CONCLUSION: PLR was altered following participation in competitive rugby union. The lower NPi and DV values post-match suggest a change in autonomic brain function, in keeping with studies where concussions were clinically diagnosed [1]. Anisocoria also increased pre-post, reflecting previous data from mixed martial arts sparring without incidence of diagnosed concussion [3]. PLR offers a rapid and objective measure of autonomic brain function and could be a promising tool for player assessment, but further research is needed to establish the relationship of PLR to the number and severity of head impacts and the decay of these changes.